An Educational Perspective on Youth Speech Patterns in Social Interaction - Risman Iye; Karim; Muhammad Yusnan; Irman Matje (Jurnal Wawasan Sarjana, 2025)
This study is motivated by the changing patterns of youth speech in the digital era, which are increasingly dynamic and tend to shift toward informal language use. The rapid development of technology and social media has significantly influenced communication practices, giving rise to phenomena such as code-mixing and inconsistencies in linguistic politeness. This condition is important to examine from an educational perspective, particularly in efforts to develop ethical and well-structured language behavior. The study aims to analyze speech patterns in social interactions and to identify the factors influencing them. The research employs a descriptive qualitative approach to gain an in-depth and contextual understanding of speech pattern phenomena. Data were collected through participant observation, semi-structured interviews, and documentation to ensure rich and valid information. Data analysis follows the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification conducted iteratively to ensure credible and comprehensive findings. The findings indicate that speech patterns tend to be informal, involve code-mixing in communication, and show inconsistency in linguistic politeness. Technological advancement and social environment emerge as the main factors shaping these communication patterns. The study concludes that strengthening language education through more adaptive and contextual approaches is necessary to enhance language awareness, enabling individuals to communicate politely, effectively, and responsibly.